Savoir-faire et franchise - Nadal, Mathieu (Université Côte d'Azur, 2020)
A l’instar de l’obligation d’assistance ou de la mise à disposition de signes distinctifs, le savoir-faire constitue un élément essentiel du contrat de franchise. En dépit de son importance, le législateur a fait le choix de ne pas le définir. Il est donc revenu à la jurisprudence ainsi qu’à la doctrine de dégager les éléments constitutifs du savoir-faire. Par ailleurs, l’importance du savoir-faire au sein du contrat de franchise se matérialise à travers l’étendue des obligations que chacune des parties devra supporter tout au long de la relation contractuelle. En raison de sa valeur patrimoniale importante, le franchiseur devra prendre toutes les mesures qui s’imposent afin de préserver son savoir-faire. Le franchiseur pourra avoir recours à différentes actions, civiles ou pénales, afin d’obtenir d’une part, la réparation de son préjudice et d’autre part, la condamnation de l’auteur de l’atteinte au savoir-faire.
Keywords: Circuits de distribution; Concessions (commerce de détail); Responsabilité contractuelle; Savoir-faire industriel

Consumer protection in an electronic environment - Akhigbe, Iyen Joy (University of South Africa, 2020)
Consumer protection laws have not evolved on par with the development of electronic media. As a result, consumer protection laws do not address all major areas of legal concern that affect the electronic commerce (e-commerce) consumer. Furthermore, differing laws in the area of consumer protection make harmonised consumer protection neigh on impossible. Currently, there is a plethora of laws on the protection of consumers but most of these laws are within the sphere of conventional consumer protection legislation which does not adequately address the legal challenges posed by the proliferation of electronic transactions (e-transactions). Specific e-transaction laws are now to be found in certain international and regional documents emanating from organisations including: the United Nations (UN); the Council of Europe; the Organisation for Economic Cooperation and Development (OECD); the African Union (AU); the Economic Community of West African States (ECOWAS); the Southern African Development Community (SADC); the Common Market for Eastern and Southern Africa (COMESA); and the East African Community (ECA). These legal instruments have already been implemented in certain states’ national legislation, while other countries have yet to accede to them. Despite these legal instruments, e-commerce consumers are faced with inadequate or obsolete legislative provisions and are yet to enjoy full protection equivalent to that accorded to the “traditional” consumer. Furthermore, given the trans-national nature of the internet, divergent laws will inevitably prove to provide inadequate protection to e-commerce consumers. In this research, international and regional legislative instruments, as well as the national laws of selected countries such as the United States (US), the United Kingdom (UK), the Republic of South Africa (South Africa), the Federal Republic of Nigeria (Nigeria), and the Commonwealth of Australia (Australia) are examined. The strengths and gaps in each of these instruments and laws are identified with the aim of harmonising the principles they espouse in a single, cogent, and comprehensive body of rules which could take the form of an international convention. An international convention should be based on national and international best practices. The national adoption of the minimum standards espoused in the proposed Convention will ultimately, promote harmonisation.
Keywords: Borderless jurisdiction; Cooling-off; Cyberspace; E-agent; E-commerce consumer rights; Electronic transferable record; Hidden charges; Information; Keystroke error; M-commerce; Shrinkwrap; Single window facility; Terms and conditions; Transaction; Web-wrap; Wireless Application Protocol

الإشهار الخادع: دراسة مقارنة - موسى, نسيمة (Ibn Khaldun University of Tiaret, 2020)
يدور المحور الرئيس للموضوع حول جريمة الإشهار الخادع دراسة مقارنة بين كل من التشريع الجزائري والفرنسي والمصري، حيث يمكن إعطاء تعريف لهذه الجريمة على أنها إعلان يتضمن عرضا، او بيانا أو إدعاء كاذب ومضلل، أو أي أمر يؤدي بطريقة مباشرة أو غير مباشرة إلى خلق إنطباع حقيق أو مضلل، أو تقديم معلومات غير دقيقة وبالتالي تؤدي إلى إنطباعات مخادعة تغري المستهلكين بالشراء بناءا على تلك المعلومات، لذلك عملت مختلف التشريعات على وضع ضوابط العمل في المجال الإشهاري وهو ماتصدى له المشرع الجزائري من خلال جملة من النصوص القانونية التي أوردها في كل من القانون رقم 04/02 المتعلق بالقواعد المطبقة على الممارسات الأنشطة التجارية لاسيما المادة 28 منه، بالإضافة إلى قانون العقوبات مع العلم أنه في الجزائر لا يوجد قانون خاص بالإشهار على عكس التشريعين الفرنسي والمصري حيث يوجد لديهم قانون خاص ينظم عملية الإشهار، ولمعرفة الحماية المكفولة للمستهلك منها سوفى نتولى دراستها من الجانب المدني أي الحماية المدنية ثم الشق الجزائي أي الحماية الجنائية.
Keywords: Biens; Criminalité; Marketing; Protection juridique; Protection pénale; Publicité; Services; Tromperie